Avaliação da utilização de resíduos grits da indústria de papel e celulose na produção de ligantes álcali ativados - Oliveira, Leandro Danilo (2022)
In the present work, the potential use of grits, waste from the pulp and paper industry generated in the Kraft process, in the production of activated alkali binders was evaluated. The grits were heat treated in order to make them more reactive. Activated alkali ligands are constituted by the C-A-S-H gel, which require calcium oxide in their composition for their formation. This work proposed parameters for the heat treatment of the grits, in order to decarbonate the calcite and verify the reactivity of the resulting component, calcium oxide, in the mixture. The heat treatment results were efficient, demonstrating that high levels of calcium oxide were generated. Activated alkali binders based on metakaolin and heat-treated grits were produced, using as activating solution: sodium silicate, sodium hydroxide and water. The activated alkali ligands produced have a Na2SiO3/NaOH ratio of 2.5 and a water/(metakaolin+grits) ratio of 0.50. In the dosage of activated alkali binders, the percentage of metakaolin replacement by grits varies from 0 to 50%, the proportion of activators in dry mass from 0.4 to 1.0 and curing time from 2 to 28 days. The variation of the molar ratio of oxides was 0,00 ≥ 2 ≤ 1,19, 0,14 ≥ 22 ≤ 0,49. Twenty-two experiments were carried out, having as answers the tests of mini slump, compression, water absorption, void index and specific mass. he results obtained in this work demonstrate that Thermally Treated Grits (GTT) residues have the potential to replace metakaolin by up to 50% and be used in the production of activated alkali ligands. The activated alkali binder with 20% replacement of metakaolin by GTT and proportion of activators equal to 0.6 showed the best compressive strength (21.86 MPa). The highest spreading, lowest water absorption and void index were obtained in pastes with 50% metakaolin replacement by GTT and activator proportion equal to 0.7. The mixtures studied with replacement of up to 50% of metakaolin by GTT showed good physical properties, demonstrating the technical feasibility of using residue grits from the pulp and paper industry for the production of activated alkali binders.